2015
DOI: 10.1093/scan/nsv080
|View full text |Cite
|
Sign up to set email alerts
|

Externalizing proneness and brain response during pre-cuing and viewing of emotional pictures

Abstract: Externalizing proneness, or trait disinhibition, is a concept relevant to multiple high-impact disorders involving impulsiveaggressive behavior. Its mechanisms remain disputed: major models posit hyperresponsive reward circuitry or heightened threat-system reactivity as sources of disinhibitory tendencies. This study evaluated alternative possibilities by examining relations between trait disinhibition and brain reactivity during preparation for and processing of visual affective stimuli. Forty females partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 55 publications
1
17
0
Order By: Relevance
“…Although state affect was not assessed in the current study, the present findings provide indirect, laboratory-based support of this putative mechanism and offer insight into methods that might attenuate it. Consistent with prior work (Foell et al, 2016), it is reasonable to presume that trait disinhibition facilitated heightened negative affect in response to high provocation. Given this, the fact that the distraction manipulation attenuated the positive association between trait disinhibition and aggression under high provocation carries important significance.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Although state affect was not assessed in the current study, the present findings provide indirect, laboratory-based support of this putative mechanism and offer insight into methods that might attenuate it. Consistent with prior work (Foell et al, 2016), it is reasonable to presume that trait disinhibition facilitated heightened negative affect in response to high provocation. Given this, the fact that the distraction manipulation attenuated the positive association between trait disinhibition and aggression under high provocation carries important significance.…”
Section: Discussionsupporting
confidence: 74%
“…A wealth of literature indicates that individuals who are high in trait disinhibition display heightened reactivity to negative stimuli (Cyders & Smith, 2008;Foell et al, 2016;Patrick et al, 2013;Sher & Trull, 1994;Taylor et al, 1999). A wealth of literature indicates that individuals who are high in trait disinhibition display heightened reactivity to negative stimuli (Cyders & Smith, 2008;Foell et al, 2016;Patrick et al, 2013;Sher & Trull, 1994;Taylor et al, 1999).…”
Section: A Proximal Mechanism: Attention To Negative Affectivitymentioning
confidence: 99%
See 1 more Smart Citation
“…A core advantage is that trait dimensions structured in this way can be expected to covary more strongly and reliably with other measures from the neurobiological modality (for direct evidence of this, see Patrick et al, 2013b;Venables et al, 2018;Yancey et al, 2016). With regard to the current study, for example, the configuration of traits shown to interface effectively with the P3 brain response factor would be expected to correlate more robustly and consistently with other brain-based measures of externalizing proneness-including neuroimaging measures (e.g., Castellanos-Ryan et al, 2014;Foell et al, 2016) as well as other ERP measures (e.g., Hall, Bernat, & Patrick, 2007)-while also relating robustly to disinhibitory clinical conditions (see Figure 2). Improvements in the ability to identify replicable associations between psychological and neural-response measures are greatly needed to permit progress in understanding the role of neurobiological systems/ processes in mental illness.…”
Section: Biobehavioral Externalizing Liability and The Ampdmentioning
confidence: 65%
“…Besides relating more strongly to electrocortical and visceral-somatic indices of psychopathology-relevant processes, psychoneurometric assessments can be expected to predict more robustly to brain activations occurring during cognitive and emotional tasks in neuroimaging contexts (e.g., Foell et al, in press; Vizueta et al, 2012), and potentially to affiliated neuroanatomical and neurochemical variables. At the same time, use of scale-report measures together with physiological measures as indicators ensures that these trait assessments remain tied to clinical problems that are most commonly assessed in the psychological domain (Patrick et al, 2013; Yancey et al, 2016).…”
Section: Discussionmentioning
confidence: 99%